2020
DOI: 10.21307/eb-2020-001
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and/or Mental Illness: A Scoping Review of the Evidence and Implications of the Dual-Continua Model of Mental Health

Abstract: The dual-continua model of mental health suggests that mental illness and positive mental health reflect distinct continua, rather than the extreme ends of a single spectrum. The aim of this review was to scope the literature surrounding the dual-continua model of mental health, to summarise the evidence, highlight the areas of focus for individual studies and discuss the wider implications of the model. A search was conducted in PsycINFO (n = 233), PsycARTICLES (n = 25), Scopus (n = 137) and PubMed (n = 47), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
158
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(181 citation statements)
references
References 40 publications
13
158
0
10
Order By: Relevance
“…Improving access to internet-based services can act as an important complement to face-to-face measurement methods, as it may reduce barriers to seeking help [42]. Harnessing internet-based innovations in mental health service provision can stimulate wider mental health reform and help strengthen services for the entire population, regardless of the presence of (severe) mental disorders [43]. This is particularly important in relation to access to mental health services for vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…Improving access to internet-based services can act as an important complement to face-to-face measurement methods, as it may reduce barriers to seeking help [42]. Harnessing internet-based innovations in mental health service provision can stimulate wider mental health reform and help strengthen services for the entire population, regardless of the presence of (severe) mental disorders [43]. This is particularly important in relation to access to mental health services for vulnerable groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, mental health does not exist on one continuum with mental illness and mental well-being (absence of mental illness) sitting at opposite ends of the same spectrum. Rather, as the dual-continua model of mental health suggests, mental illness and mental well-being exist on two distinct continua [ 44 , 45 ] and changes in levels of mental well-being are a predictor of future risk of mental illness (e.g., losses of mental well-being predict increases in mental illness, while gains in mental well-being predict declines in mental illness) [ 46 ]. Failure to consider this complexity in mental health may mean that adverse consequences for mental well-being, that undermine quality of life without rendering a person mentally ill at the time, are overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of hypotheses can be formulated to account for these outcomes: maybe the differences are related to differences in patient samples, the use of specific measures (BSI versus OQ-45 and SMI), of differences in study design (we did not study the effects of an art therapy intervention and did not calculate effect sizes). In addition, a recent scoping review of Lasiello et al (2020) identified a considerable body of empirical research investigating the validity of the dual-continua model, and the overarching notion that positive mental health and mental illness represent two distinct, yet related, constructs. They strongly advocate assessing positive mental health and mental illness together, rather than using only one or the other.…”
Section: Discussionmentioning
confidence: 99%